Effects of DTP Vaccination on Ravet Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
An association between DTP vaccination and onset of seizures in 40 patients diagnosed with Dravet syndrome was investigated by retrospective analysis of medical and vaccination records at Heidelberg Hospital, Victoria, Australia.